2008
DOI: 10.1586/14760584.7.5.547
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid vaccination: the Asian experience

Abstract: The WHO has recently issued updated recommendations for the programmatic use of new-generation typhoid vaccines in high-risk areas of countries where typhoid fever is still endemic. Countries have subsequently been instructed to discuss how these recommendations can be implemented and to develop plans for targeted typhoid vaccination. These plans can be informed by the experiences with typhoid vaccination that several Asian countries have had. This article reviews past and current typhoid vaccination programs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…Typhoid is generally believed to be a disease of older children but studies have indicated that typhoid causes significant morbidity and mortality in children below five years of age [3][4][5]. Vaccination is recommended as a key intervention in the control of typhoid fever [6] especially given the emergence of multidrug resistant strains of S. Typhi [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Typhoid is generally believed to be a disease of older children but studies have indicated that typhoid causes significant morbidity and mortality in children below five years of age [3][4][5]. Vaccination is recommended as a key intervention in the control of typhoid fever [6] especially given the emergence of multidrug resistant strains of S. Typhi [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Vi-DT was stable under repeated freeze-thaw (20 cycles). We plan to perform clinical evaluation of the safety and immunogenicity of Vi-DT when added to the infant combination vaccines.Typhoid fever, a serious systemic infection caused by Salmonella enterica serovar Typhi, remains a major public health problem in Central Asia, Southeast Asia, Africa, and Latin America (11,52,53). It was estimated that more than 21 million cases of typhoid fever and Ͼ200,000 deaths occurred in 2000 (10).…”
mentioning
confidence: 99%
“…A similar outcome has been observed in China where targeting of high incidence areas resulted in decreased typhoid incidence. 11 In Cakaudrove subdivision (65% vaccinated), incidence decreased post-campaign, but the proportion of cultures positive for Typhi and the number of hospitalized cases was similar before and after the campaign. It is not possible for us to assess whether ongoing typhoid in Cakaudrove is occurring primarily within unvaccinated areas, or whether the local epidemiology or targeting strategy made the campaign less effective than in other subdivisions.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, data have become available from typhoid vaccination programs in Thailand, China, Vietnam, and India, and large-scale vaccine demonstration projects in five Asian countries that have confirmed the effectiveness of vaccines for reducing typhoid in endemic, highincidence settings. 11,[18][19][20][21] Typhoid vaccination can also be considered in other high-incidence settings, along with comprehensive typhoid control measures. …”
Section: Discussionmentioning
confidence: 99%